Maintenance for Blood Relatives (Collaterals) under Islamic Law in Malaysia: (Nafkah Saudara Sedarah Sesisi (Hawashi) dalam Undang-Undang Islam Di Malaysia) (Kanun: Jurnal Undang-undang Malaysia, 2020)
Under Islamic law, blood relatives from among hawashi (collateral kin) fall into the category of those who deserve nafaqah (maintenance), especially whenever they are in need or when they are incapable of maintaining themselves, while at the same time having relatives who are capable and well off. This research discusses maintenance for collateral relatives as an instrument to ensure continuous protection of relatives under Islamic law. The discussion includes the views of the fuqaha on maintenance to hawashi in Islam. It also reviews the basis for the responsibility to maintain relatives including relevant principles in the Quran and the Sunnah of the Prophet SAW, the discussion and views of contemporary fuqaha (Islamic jurists) on the extent of a person's responsibility to maintain relatives. Further, this research also analyses the application of Islamic law in Malaysia in relation to one's responsibility to maintain relatives. For the purpose of comparison, discussion will also include provisions of the law on maintenance for relatives in several Muslim countries. The research was conducted through library research and analysing the treatises of Muslim jurists, as well as the provisions of Islamic law on maintenance for collateral relatives. The findings of this research are deemed significant to improve the existing provisions on Islamic law relating to maintenance in Malaysia.Keywords: Nafaqah, Islamic law, sibling maintenance, hawashi, Malaysian sharia law, Muslim countries